Misquoting Jesus: the story behind who changed the Bible and why - Ehrman, Bart D. (HarperSanFrancisco, 2005)
When Biblical scholar Ehrman first began to study the texts of the Bible in their original languages, he was startled to discover the multitude of mistakes and intentional alterations that had been made by earlier translators. For almost 1500 years these manuscripts were hand copied by scribes who were influenced by the cultural, theological and political disputes of their day. Both mistakes and intentional changes abound in the surviving manuscripts, making the original words difficult to reconstruct. Ehrman reveals where and why these changes were made and how scholars go about reconstructing the original words of the New Testament as closely as possible. He makes the provocative case that many of our cherished biblical stories and beliefs stem from both intentional and accidental alterations by scribes--alterations that dramatically affected subsequent versions.--From publisher description